Radix entomolaris – A case report - Felipe Davini; Rodrigo Sanches Cunha; Carlos Eduardo Fontana; Claudia Fernandes de Magalhães Silveira; Carlos Eduardo da Silveira Bueno (Revista Sul-Brasileira de Odontologia, 2013)
A comprehensive knowledge on the root canal anatomy is a basic prerequisite for the endodontic treatment successful. Mandibular molars may have an additional root located lingually (radix entomolaris) or buccally (radix paramolaris). In the literature, this anatomy variation is considered rare in Caucasian populations. Awareness and understanding of the presence of unusual external and internal root canal morphology contributes to the successful outcome of the root canal treatment. Objective and case report: The purpose of this study was to report a clinical case of successful endodontic treatment in a mandibular molar with pulp necrosis and characterized as radix entomolaris in which the use of magnification and ultrasonic tips (the “microsonics concept”) was fundamental to the management of the variations in the internal anatomy. Conclusion: A better understanding of the root canal morphology is essential for endodontic treatment success, as well as the use of technologic advancements in Endodontics including computed tomography, ultrasonic tips and the operating microscope.